P-graph approach to optimizing crisis operations in an industrial complex - Tan, Raymond Girard R. (Animo Repository, 2016)
Industrial complexes allow for efficient and sustainable production of various goods, but at the same time they are also vulnerable to cascading failures caused by disruptions in process capacity or resource availability. Climate change in particular may cause significant perturbations in the supply of important process inputs such as water, energy, or feedstocks. Thus, for industrial complexes, proper risk management strategies must be developed as part of overall climate change adaptation and resilience measures. Rigorous modeling approaches are needed to ensure that economic losses resulting from a disruption are minimized. In this paper, a P-graph-based methodology is used to determine optimal adjustments to crisis conditions in order to minimize manufacturing losses; this graph theoretic methodology has traditionally been used for process network synthesis problems but has recently proven to be useful for structurally analogous problem domains. Two case studies on the reallocation of production capacities and product streams in an aluminum production complex and a biomass processing complex are used to illustrate the methodology. © 2015 American Chemical Society.